‘Living in a state of filth and indifference to … their health’: Weather, public health and urban governance in colonial George Town, Penang - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2020)
This article explores the development of public health infrastructure in George Town, Penang, before the 1930s. It argues that the extreme weather of the tropical climate led to a unique set of health challenges for George Town’s administrators, as the town grew from a small British base to a multi-cultural and thriving port. Weather and public health were (and still are) integrally connected,although the framing of this relationship has undergone significant shifts in thinking and appearance over time. One lens into this association is the situation and expression of these elements within municipal structures.During the nineteenth century, government departments were fewer and shared roles and responsibilities. The Medical Department, for example, observed the weather, making connections between rain, drought and the incidence of disease. Engineers asked critical questions about mortality rates from disease after floods. As ideas about climate and health developed and changed, the shift became evident in the style, concerns and proliferation of governmental departments. This article thus considers the different ways in which weather,public health, and town planning were understood, managed and enacted by the Straits Settlements’ administration until the 1930s.